Neoproterozoic orogeny along the margin of Rodinia: Valhalla orogen, North Atlantic - Cawood, P.; Strachan, R.; Cutts, K.; Kinny, Peter; Hand, M.; Pisarevsky, S. (Geological Society of America Inc, 2010)
Latest Mesoproterozoic to mid-Neoproterozoic (1030–710 Ma) sedimentation and orogenic activity that developed on the northeast Laurentian substrate around the North Atlantic borderlands and is currently exposed in Scotland, Shetland, East Greenland, Svalbard, and Norway, is herein defined as the Valhalla orogen. The site for the orogen was initiated by ∼95° of clockwise rotation of Baltica with respect to Laurentia at the end of the Mesoproterozoic. This created a triangular ocean basin, the Asgard Sea, which received orogenic detritus from the Grenville-Sveconorwegian-Sunsas orogen.Sedimentary successions within the orogen accumulated during two cycles at 1030–980 Ma and 910–870 Ma, with each cycle terminated and the successions stabilized during tectonothermal episodes involving crustal thickening and igneous activity, some of calc-alkaline affinity, associated with the Renlandian (980–910 Ma) and Knoydartian (830–710 Ma) orogenic events. The Valhalla orogen represents an exterior accretionary orogen that developed along the margin of Laurentia and the Asgard Sea. The early stages of the Valhalla orogen are coeval with the final stages of the Grenville-Sveconorwegian-Sunsas orogen to the south, but are tectonically discrete; they constitute part of an exterior orogen that is entirely distinct from the interior orogen formed between collision of Laurentia, Baltica, and Amazonia.